Impact of classical massage on temperature, strength and flexibility of upper limbs muscles in healthy men - Boguszewski, Dariusz; Adamczyk, Jakub Grzegorz; Andersz, Nina; Mrozek, Natalia; Piejko, Karolina; Janicka, Małgorzata; Białoszewski, Dariusz (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Thermography is a one of new non-invasive method using to assess the impact of physiotherapeutic treatment for the human body. Aim of Study. The purpose of this study was the qualification of dependence between application of classical massage of hand and forearm and the temperature of muscles surface of the upper limb and the strength of hand and the range of motion in radio-carpal joint. Material and Methods. The research embraced 12 men aged 19-23 years. The Flir A325 camera was used for thermal imaging. The measurement of hand strength was made by means of analog dynamometer, and the range of motion in radio-carpal joint – was measured with the goniometer. All tests and measurements were performed twice – directly before and after the massage of hand and forearm (the right limb).Classical massage was performed on the dorsal and palmar surface of the hand and on front and back of the forearm. Results. After the massage the superficial temperature of massaged (studied) limb significantly rose. There was also noted some essential difference of temperature of the back surface of the limb not being massaged (control). One did not, however, observe any differences of temperature of the front surface of the left forearm and shoulder. The broadening of the range of motion in radio-carpal joint of the right limb (in all surfaces) was shown. There were no characteristic differences in the hand strength measured with the dynamometer before and after applied massage. Conclusions. The classical massage, though it increases the temperature of muscles and affects the enlargement of effort tolerance, is not a sufficient means for preparation to physical effort. Due to massage, the range of motion in the joint of massaged limb broadened, therefore, the effect of applied treatment is mostly loosening
Keywords: thermography; massage; upper limbs; untrained men; hand grip; range of motion